A Multifactor Model of Banking Industry Stock Returns: An Emerging Market Perspective - Muneer, Saqib; Butt, Babar Zaheer; ., Kashif Ur Rehman (Information Management and Business Review, 2011)
The purpose of this study is to examine the stock returns variation to specific macroeconomic and industry variables by applying multi-factor model. The firms of banking industry were selected for this study on the basis of data availability, profitability and performance on the Karachi Stock Exchange. The data for the selected firms and economic variables obtained for the period of 10 years. Descriptive statistics performed for the temporal properties and GARCH model was used to analyze the risk and return relationship. The tests were applied on the stock returns of each firm and on the data set of the entire industry to generalize the results. The results reveal that market return is largely accounts variation in stock returns, however the inclusion of other economic variables has added to the explanatory power of the model. It is also found that industry stock returns are more responsive to changes in economic conditions than firm level stock returns.